Fetal and maternal manifestations of tuberous sclerosis complex: Value of fetal MRI. Issue 1 (February 2016) - Goel, Reema; Aggarwal, Nishant; Lemmon, Monica E; Bosemani, Thangamadhan
Tuberous sclerosis complex (TSC) is a genetic disorder characterized by benign hamartomas in various organ systems of the body. Prenatal screening of fetuses of mothers affected with TSC using ultrasonography (US) may detect cardiac lesions. Fetal US is not sensitive for evaluation of the brain. We describe brain MRI findings in a fetus with cardiac rhabdomyomas identified on prenatal screening US. Postnatal brain MRI at 5 days of age demonstrated fetal MRI findings without significant added information. Fetal MRI is the imaging modality of choice for evaluation of cerebral manifestations of TSC. Maternal manifestations of TSC in the abdomen or pelvis may also be demonstrated on fetal MRI.